Communication Strategy: Does the Two-Step Still Work? - F. Dale Parent; Stephen B. Lovejoy (Journal of Applied Communications, 1987)
Much of our work in cooperative extension deals with the transfer of information or technology to clientele. Therefore, it is extremely important that we use the most effective and efficient means possible in carrying out this task.